2016
DOI: 10.1016/j.virol.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Mood stabilizers inhibit cytomegalovirus infection

Abstract: Cytomegalovirus (CMV) infection can generate debilitating disease in immunocompromised individuals and neonates. It is also the most common infectious cause of congenital birth defects in infected fetuses. Available anti-CMV drugs are partially effective but are limited by some toxicity, potential viral resistance, and are not recommended for fetal exposure. Valproate, valpromide, and valnoctamide have been used for many years to treat epilepsy and mood disorders. We report for the first time that, in contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…The results of our epidemiological study are consistent, and extend to humans, with previous reports on the in vivo potential of VPA and its derivative valpromide—which lacks the free carboxylic group and the HADC inhibitory activity—to interfere with herpesvirus multiplication in mice [7]. Hence, a trend to a protective effect in human patients was observed for both compounds, although the decreased risk observed was marginally significant only for VPA ( p = 0.053).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of our epidemiological study are consistent, and extend to humans, with previous reports on the in vivo potential of VPA and its derivative valpromide—which lacks the free carboxylic group and the HADC inhibitory activity—to interfere with herpesvirus multiplication in mice [7]. Hence, a trend to a protective effect in human patients was observed for both compounds, although the decreased risk observed was marginally significant only for VPA ( p = 0.053).…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with in vitro studies showing that, in cultured cells, VPA inhibits the production of infectious progeny of different enveloped viruses causing relevant human and veterinary diseases [3,5,6,9,16,17] including herpesviruses [4,7,8].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Clozapine had no significant effect on the transcription of HERVs in three types of brain cell lines, though VPA upregulated the transcription of many HERVs [44]. Valpromide, an anti-epileptic drug that inhibits EBV lytic reactivation [5], had no effect on vesicular stomatitis virus infection [45]. Valpromide and a structurally-related molecule valnoctamide inhibited infection and replication of the human herpesvirus cytomegalovirus in cell culture, and increased the survival rate of mice infected with mouse cytomegalovirus [45].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, VPA affects lipid metabolism (including the synthesis of phosphatidylinositols) and formation of cell membranes, so it may alter the viral acquisition of lipid envelope, resulting in mature viral particles with low stability [45]. Furthermore, some studies have reported antiviral activity of VPA, VCD and VPD against cytomegalovirus (CMV), a virus belonging to the Herpesviridae family that causes brain defects in neonates, not only outside the central nervous system but also in the developing brain of rodents [65,69]. CMV attaches to the cell through interaction of its glycoprotein gB with cellular heparan sulfate proteoglycans, and both VCD and VPD appear to affect the recognition of gB [49,69].…”
Section: Antiviral Mechanism Of Vpa and Related Derivativesmentioning
confidence: 99%